Tricuspid Valve Excision Complicated by Postoperative Gerbode Defect Following Recurrent Infective Endocarditis: A Case Report. (March 2021) - Dhaliwal, Jasdeep S.; Wadle, Michael J.; Malyala, Rajasekhar; Dwarakanath, Sanjay; Hatton, Kevin W.
Tricuspid valve infective endocarditis is an increasingly common sequela of the opioid epidemic. While often managed medically, certain subsets of patients will require surgical intervention, including repair, replacement, and possibly even excision. Historically, simple valvectomy was performed in instances of recidivism and reinfection; however, reoperation and replacement has become the preferred treatment in the current era. Given the increasing incidence of intravenous drug use and the increase in the number of patients presenting with recurrent infections, simple valvectomy has regained favor in recent years. In this article, we present the management of a critically ill patient with recurrent tricuspid valve endocarditis who underwent tricuspid valvectomy that was complicated by a left ventricle to right atrium fistula and discuss some of the most important perioperative issues and complications for patients who undergo tricuspid valvectomy.